2021
DOI: 10.1002/solr.202100670
|View full text |Cite
|
Sign up to set email alerts
|

PCDTBT8‐Doped PffBT4T‐2OD‐Based Ternary Solar Cells with Enhanced Open‐Circuit Voltage, Fill Factor, and Charge Separation Efficiency

Abstract: The effect of a medium bandgap polymer doped into conventional binary heterojunction solar cells is investigated for ternary solar cells, which display different characteristics compared with traditional materials. First, the charge separation and recombination at the multi‐interface (double donors/single acceptor) and the charge transport between different phases are simulated to reveal the competition mechanism of electron transfer and insights into the merits and demerits of a hole transport layer with medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…In the processes of photocurrent generation, the interface plays a crucial role in determining the PCE of solar cell devices. Hence, the interfacial charge separation and recombination processes should be explored, as these processes at the interface will significantly affect the device’s efficiency. , According to the Marcus theory, the charge separation process corresponds to two key parameters: charge-separated transfer rate K int‑CS and charge recombination rate K int‑CR . When the K int‑CS is larger, excitons of the compound will facilitate dissociation, but the larger K int‑CR will restrict the charge separation process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the processes of photocurrent generation, the interface plays a crucial role in determining the PCE of solar cell devices. Hence, the interfacial charge separation and recombination processes should be explored, as these processes at the interface will significantly affect the device’s efficiency. , According to the Marcus theory, the charge separation process corresponds to two key parameters: charge-separated transfer rate K int‑CS and charge recombination rate K int‑CR . When the K int‑CS is larger, excitons of the compound will facilitate dissociation, but the larger K int‑CR will restrict the charge separation process.…”
Section: Resultsmentioning
confidence: 99%
“…The methyl groups replaced the flanking groups of all molecules because many studies have shown that the change of the branched chain had almost no effect on electronic structures and properties. 33,34 The investigated monomers were optimized under the B3LYP 31,35 function and 6-311G(d,p) 31,36 basis set, which can create reliable geometries and precision for mediumsized acceptors. 31,32,37 One also calculated the energy levels and compared them with the experiment to prove the rationality of the selection method (see Table S1 for different functionals).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ideal molecule should have good stability that is an important parameter to assess the molecular function of HTMs. [40] The stability is generally evaluated by absolute hardness (η), which is calculated by [41,42] η…”
Section: Stability and Solubility Of Htmsmentioning
confidence: 99%
“…In perovskite solar cells (PSCs) [5][6][7][8], stability can be increased. In dye-sensitized solar cells (DSSCs) [9][10][11][12], the conjugate system is a good electron transport material [13][14][15]. Moreover, the widely used two-dimensional material graphene [16][17][18][19][20][21][22] also has a wide range of conjugated systems.…”
Section: Introductionmentioning
confidence: 99%